Implementation of the School as a Learning Organisation Approach in Vocational Education: The Case of Latvia - Gunta Siliņa-Jasjukeviča; Ilze Briška; Inese Lūsēna-Ezera; Agnese Lastovska; Inga Linde (Acta Paedagogica Vilnensia)
Context. Recent studies recognise that the use of the School as a Learning Organisation (SLO) approach in educational management is the key factor ensuring a general education institution’s ability to effectively implement the education policy goals and adapt to change as the use of SLO. Although vocational education has different predominant goals and different target groups, likewise general education, it is exposed to dynamic change and new challenges.Purpose. Within the framework of the study, it was researched whether and how SLO can be applied in vocational education as the use of SLO facilitates a high level of professional competence of the management and academic staff, enhances common strategic vision, responsibility and autonomy, diverse collaboration, effective resource management, and the dissemination of knowledge and good practice, which are also important in vocational education.Methods. Using qualitative data analysis, the paper analyses the experience of EU and OECD countries in the implementation of SLO in vocational education and identifies, which dimensions of the SLO model are represented in the policy and practice of vocational education in Latvia. In the focus group interviews with representatives of vocational education institutions of Latvia, the characteristics of the SLO approach in vocational education were studied, challenges were described and solutions proposed for the targeted implementation of the SLO approach in vocational education in Latvia.Results. All 7 dimensions of the SLO can be found in the education policy documents of the EU and OECD countries and Latvia, as well as in the focus group interviews, which shows that there is a gradual progress towards the transformation of vocational education institutions into learning organisations.Conclusions. For education policy makers: Since the features of SLO are only partially visible in vocational education documents in Latvia, the framework should be improved to cover all dimensions of the SLO, and norms and agreements on collective understanding should be harmonised in policy documents. For school representatives: Raise awareness of the staff of vocational education institutions of the essence of the SLO and its role in improving the quality of education and ensure that all dimensions of SLO are understood and addressed appropriately. For entrepreneurs: Help define the diverse, varied manifestations of professions in the sector in order to engage the individual potential of learners as effectively as possible. For researchers: Help find ways to resolve controversies by identifying good practice and research.